Balloon expandable stents for coarctation of the aorta: Current status and technical considerations: Case report - Kritvikrom Durongpisitkul (2018)
Background: Balloon expandable stents have been used to manage coarctation of the aorta (Co) in selected patients with very encouraging results. Material and Method: The authors report here the first group of patients with Co who underwent a successful implantation of the new Palmaz Genesis™ stent with intermediate term follow up. Results: There were 5 patients with an age range from 14 to 23 years old. All of them had significant Co and were receiving multiple anti-hypertensive medications. Primary stenting was performed in all patients. All of them had an immediate relief of the gradient. All antihypertensive medications were discontinued immediately in 4 patients. All patients had one year follow up which revealed a minimum gradient. One patient continues to receive oral antihypertensive medication. Conclusion: In patients with coarctation of the aorta (native or recoarctation of aorta), stent implantation may be a feasible and improved option to relieve the stenosis. Short and mid term followup of these patients have shown encouraging results.